First record of bird and spider species preying on dung beetles (Coleoptera: Scarabaeidae: Scarabaeinae) in the Amazon Forest - Salomão, Renato P.; Valentim, Cleiton; Lira, Andre F. A. (Entomological Communications, 2026)
Predator-prey relationships are critical for establishing trophic networks, but our understanding of these interactions is hindered by a lack of records in tropical rainforest ecosystems. Although literature indicates that dung beetles may be preyed by a wide range of animal species, surprisingly, there are no such antagonistic records between dung beetles and other species in the Amazon forest. The objective of this study is to present two records of such interactions in the Amazon, involving a bird and a spider species preying on dung beetles. The bird Galbula albirostris Latham, 1790 (Aves: Galbulidae) was observed feeding on a Deltochilini dung beetle (Coleoptera: Scarabaeidae) in a terra firme forest, while a Canthidum sp. was captured in a Trichonephila sp. (Araneae: Nephilidae) spider web on an artificial island also located in a terra firme forest. While birds are the most commonly recorded predators of dung beetles in the literature, there are few records of such predation events with spider species. The scarcity of data regarding predatory behavior on dung beetles in the Amazon forest underscores the need to assess these interactions to establish their importance in maintaining food webs.